TINGKAT KEBUGARAN AEROBIK KORPS POM TNI AU DITINJAU DARI LARI 12 MENIT (Studi Empiris pada Siswa Sekolah Kejuruan Korps Polisi Militer di Skadik 404 Lanud Adi Soemarmo): TINGKAT KEBUGARAN AEROBIK KORPS POM TNI AU DITINJAU DARI LARI 12 MENIT (Studi Empiris pada Siswa Sekolah Kejuruan Korps Polisi Militer di Skadik 404 Lanud Adi Soemarmo) - Sudrajat, Surya; Jariono, Gatot; Nurhidayat, Nurhidayat (Universitas Hamzanwadi, 2025)
This study aims to evaluate the aerobic fitness level of Sejurba POM AU 2024 students through a 12-minute running test. The method used is descriptive qualitative, which explains current facts and phenomena, with a comparative research design. The population in this study were all military police corps students at squadik 405 at Adi Soemarmo Air Base as many as 50 people and the sample in this study were 35 Sejurba POM AU students. Data collection techniques and instruments used by researchers are through exams (tests) running 12 minutes. Based on data analysis, the results show that the aerobic fitness level of Sejurba POM AU 2024 students, as measured through a 12-minute run, is categorized as “Good”. On average, 30 students fell into this category, while 5 students fell into the “Excellent” category. With the majority of students falling into the “Good” category, this reflects a positive achievement for the Sejurba POM AU 2024 students and shows good development in 12-minute running ability. It is concluded that the aerobic fitness level of Sejurba POM AU 2024 students, as assessed through the 12-minute run test, is in the Good category.